2017
DOI: 10.21767/2171-6625.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in Multiple System Atrophy of Cerebellar and Parkinsonian Types

Abstract: Objective: This study aimed to examine the relationship between dysphagia and activities of daily living (ADL) in patients with multiple system atrophy (MSA), and to characterize dysphagia in patients with the cerebellar (MSA-C) and parkinsonian (MSA-P) types.Methods: Sixty-one MSA patients (25 males, 36 females; 40 MSA-C, 21 MSA-P; mean age, 66.3 ± 11.0) were recruited. ADL was assessed on the Barthel index. They underwent tongue pressure measurements and videofluoroscopy (VF) by swallowing barium gelatin jel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Dysphagia may influence the association between ADL deterioration and the survival time. In fact, the disease duration and ADL were shown to be correlated with the dysphagia score, particularly with the pharyngeal phase score of MSA with predominant parkinsonism (101).…”
Section: Strategy For Rapidly Progressive Dysphagia In Prd Psp and Msamentioning
confidence: 95%
“…Dysphagia may influence the association between ADL deterioration and the survival time. In fact, the disease duration and ADL were shown to be correlated with the dysphagia score, particularly with the pharyngeal phase score of MSA with predominant parkinsonism (101).…”
Section: Strategy For Rapidly Progressive Dysphagia In Prd Psp and Msamentioning
confidence: 95%
“…Therefore, timely identification of dysphagia and intervention is essential to avoid complications. Nevertheless, studies objectively evaluating dysphagia in MSA are rare, and symptoms so far were assessed only by videofluoroscopic swallowing studies (VFSSs), manometric methods, or electrophysiological methods in small cohorts 4,11‐16 …”
mentioning
confidence: 99%
“…Instrumental findings of oral phase dysfunction included delayed bolus transport from the oral cavity to the pharynx, insufficient movement of the tongue base, and disturbance of bolus holding in the oral cavity. Pharyngeal phase impairment included slowed upward relocation of the larynx, vallecular residue, constriction of the pharynx and pyriform sinus residue [20][21][22]24].…”
Section: Diagnosis Of Dysphagia In Msamentioning
confidence: 99%
“…Further in the early stage of the disease, the swallowing dysfunction induced by parkinsonism in MSA-P patients appears worse than the dysfunction induced by cerebellar impairment in MSA-C patients, and progressive worsening of dysphagia in MSA-C seems related to overlapping parkinsonism [12,21,24]. A recent cross-sectional and longitudinal study retrospectively comparing the progression of oropharyngeal dysphagia in MSA subtypes found that patients with MSA-P required diet modification earlier than those with MSA-C, but no significant difference between the two groups was found in the latency of tube feeding onset [25].…”
Section: Diagnosis Of Dysphagia In Msamentioning
confidence: 99%
See 1 more Smart Citation